Shift and Equivalence of Noun Phrases in English-Indonesian Translation of Barbie Short Stories - Nikmatu Rupiah, Sri; Hartono, Rudi (Universitas Negeri Semarang, 2017)
Process of translating noun phrases from English into Indonesian causes a translator has a difficulty in determining structure of noun phrase in target language because of the different structure between both languages. This reason caused translation shifts and equivalence occur to get the appropriate meaning. Shift according to Catford is regarded as the change of formal structure of the source language into target language (cited in Venuti, 2000) while Nida regards the concept of equivalence as best translation which does not sound like translation (cited in Venuti, 2000). Most of researcher conducted shift and equivalence on Indonesian noun phrase into English translation. This study is about shift and equivalence of noun phrases in English-Indonesian translation of Barbie short stories. Therefore, there are types of equivalence and two translation shifts that must be enalyzed, namely level shift, and category shift and its sub categories; structure shift, class shift, unit shift, and intra system shift. To obtain the data, this study applied descriptive qualitative approach. The data which have been gathered were described and suited with the aim of this study. The findings map out the high use of translation shift than equivalence applied. The use of translation shift makes the translation of noun phrases more naturally and acceptable. The use of category shift, i.e. structural shift was the highest step in process of translating Barbie short stories. While the highest equivalence occurs on textual equivalence where there was equivalence structuring of a text. This study provided suggestions regarding to the implications of this study. For English language learners, they have to learn translation shift in order to understand message from target language properly. Relating to the equivalence, form and meaning were frequently not fully equivalent, but one should be noticed that forms may change but meaning must not change. In dynamic equivalence, although the form was different, but the meaning was the same.